2020 IEEE Frontiers in Education Conference (FIE) 2020
DOI: 10.1109/fie44824.2020.9273923
|View full text |Cite
|
Sign up to set email alerts
|

Exploring students’ identity development from the perspective of study difficulties

Abstract: This work-in-progress paper in research category reports preliminary findings on how students taking introductory computing courses develop identity from the perspective of study difficulties. The motivation was that students identified lack of meaning and prospects (cf. identity) as a study difficulty in a previous qualitative study. The present study further explores this finding by issuing both an identity development and a selfefficacy scale to a larger first-year student cohort. The aim is to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…We can compare the observations and attributes in these two studies with other kinds of results. Isomöttönen et al (2020) investigated students' identity development and found that many students currently studying on a first programming course doubted or were uncertain of the direction of their lives. Furthermore, Jones et al (2010) observed a decrease in several attributes (expectancy, interest, utility, self-efficacy, attainment, identification) during first-year engineering studies.…”
Section: Self-efficacy and Performance And Other Motivation-related A...mentioning
confidence: 99%
“…We can compare the observations and attributes in these two studies with other kinds of results. Isomöttönen et al (2020) investigated students' identity development and found that many students currently studying on a first programming course doubted or were uncertain of the direction of their lives. Furthermore, Jones et al (2010) observed a decrease in several attributes (expectancy, interest, utility, self-efficacy, attainment, identification) during first-year engineering studies.…”
Section: Self-efficacy and Performance And Other Motivation-related A...mentioning
confidence: 99%